Assessing Community Extension Initiative in Developing Culture-Based IPEd for Teachers and Learners in Sultan Kudarat, Philippines - Arciosa, Ramil M.; Llanillo, Lovelyn C.; Lorio, Anneril R.; Gallego, Mary Grace; Meriales, Leizel; Dardo, Armando; Valdez, Dennis; Perfecio, Jonalyn; Aguil, Noriana (UI Scholars Hub, 2025)
One of the tenets of higher education is the extension of the community that responds to the social and cultural surroundings, including the Indigenous Peoples (IP) and their rights to education. A supportive and relevant education with respect to cultural identity becomes important. This study aims to assess a community extension initiative at its preliminary stage in developing IPEd in the Philippines based on the teachers’ and learners’ awareness level of such programs. The study was conducted in two IPEd schools, Manirub Integrated School and Ugis Elementary School, at Esperanza, Sultan Kudarat. The study examined the teachers’ and learners’ awareness level related to the IPEd, including its association with the learners’ Intelligence Quotient (IQ) and Emotional Quotient (EQ), providing a basis for developing culture-based education pedagogy. The research employed statistical curve regression analysis using SPSS software. The study identifies several challenges in implementing IPEd that are related to teaching materials and the integration of cultural values and beliefs. Furthermore, there is a need to consider the IP learners' intellectual and emotional readiness, which is influential for responding to learning programs. The result also shows that the IPEd learners of both schools have a positive response to the IPEd teachers after undergoing training for a culture-responsive teaching pedagogy. Such a community extension initiative becomes crucial to assist teachers in developing the culture-based education programs for preparing the IP learners to have a future success in learning and in maintaining their cultural identity as an indigenous people from Teduray or Manobo Dulangan.